ANALISIS RASIO PROFITABILITAS PADA BANK TABUNGAN PENSIUNAN NASIONAL, TBK PERIODE 2017 - 2021 - Qhusnul Gina Wulandari, (2023)
Profitability is generally the main goal and a benchmark in a company. The level of maximum profit can be measured using profitability formula calculations. This research aims to measure the profitability of Bank BTPN for the period of 2017-2021 as the research subject based on Financial Statements and Annual Reports of the subject using Operating Expense to Operating Income (BOPO), Return on Assets (ROA) and Return on Equity (ROE). The techniques used are documentation and literature review. The results show that the BOPO, ROA and ROE of PT Bank BTPN (2017-2021) are above 51 percent, indicating a very bad performance. The profitability ratio in generating income is very low and requiring an evaluation of previous performance in order to improve future performance to gain maximal profit.